ANALISIS PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATAN KINERJA PERUSAHAAN DI ASUKA ENGINEERING INDONESIA - Yafi’ul Ammar Yulma; Sofiah (Journal of Principles Management and Business, 2025)
This study examines the implementation of Human Resource Management (HRM) strategies in enhancing employee performance, using PT. Asuka Engineering Indonesia as a case study. Employing a qualitative approach with in-depth interviews, direct observation, and documentation analysis, the research explores how recruitment, training, and performance evaluation systems contribute to organizational productivity. The findings reveal that the two-stage recruitment process, project-based training, and continuous performance assessment have successfully created an adaptive and collaborative work environment. These practices align individual competencies with organizational goals, improving efficiency and motivation. The study also highlights that leadership involvement and consistent evaluation strengthen employee engagement and professional development. From a practical perspective, this research provides insights into effective HRM implementation for construction companies aiming to enhance competitiveness through human capital optimization. The results can serve as a model for similar industries seeking sustainable performance improvement. Strategic HRM integration plays a crucial role in achieving long-term organizational growth and operational excellence.